Analisis Kebutuhan Rohani dan Strategi PAK bagi Remaja dan Pemuda di GKE Betang Kahanjak - Siska Panduwinata; Margareta Margareta; Wandi Wandi (Asosiasi Riset Ilmu Pendidikan Agama dan Filsafat Indonesia, 2025)
Spiritual needs during adolescence are very important because this time in life helps shape who a person is, how they feel, and their beliefs. This study looks at the spiritual needs of teenagers and young people at GKE Betang Kahanjak Palangkaraya, and explores ways that Christian Religious Education (PAK) can help them grow spiritually. By looking at existing research and observing the local context, the study finds that young people need support in their personal spirituality, their Christian identity, building relationships, getting guidance, becoming stronger in tough situations, and making good moral choices. Good PAK approaches include mentoring that focuses on relationships, studying the Bible in a way that fits their situation, using digital tools for spiritual growth, combining service with learning, and guidance that builds strong character. Churches need to keep up with how young people are changing and create new ways of ministry that really help teenagers and young adults grow spiritually.